The Eligibility of the Encyclopedia of Circulatory System Diseases and Disorders Based on Traditional Medicinal Plants for Hypertension as Learning Media - Youva Kristi*; Ruqiah Ganda Putri Panjaitan; Asriah Nurdini Mardiyyaningsih (Universitas Syiah Kuala, 2023)
Learning media is an essential element to support the success of learning activities. It is used stimulate the thoughts, feelings, attention, and interest of students to learn. Learning media can be developed by adding concepts and photos from the results of a research. The purpose of this study was to determine the feasibility of the encyclopedia of circulatory system diseases and disorders as a learning media. The content of encyclopedia contains the result from the inventory of medicinal plants for hypertension at Babane Village, Bengkayang, Indonesia. This study applied a research and development method. This development procedure refers to the Sugiyono development model, which consists of five stages namely potential and problems, data collection, product design, design validation, and design revision. The validity of the encyclopedia was obtained through content validation executed by five experts in the field of both biology and learning media. Encyclopedia validation is reviewed from four aspects: content, presentation, language, and graphics. Validation analysis applied the Lawshe's content validity ratio (CVR) and content validity index (CVI) approach. The results showed that the average of CVR was 1.00 which result in the CVI value of 1.00 in the